Managing preoperative anemia: Evolving concepts and strategies for improving patient outcomes. Issue 2 (June 2020) - Mosieri, Chizoba; Chandler, Debbie; Reed, Devin S.; Craig, Madelyn K.; Hyatali, Farees; Kallurkar, Anusha; Cornett, Elyse M.; Urman, Richard D.; Kaye, Alan D.
Abstract : Anemia is the most common hematological disease, and is defined by the World Health Organization as a condition in which the number of red blood cells and consequently oxygen-carrying capacity is insufficient to meet the physiological needs of the body. Anemia can occur throughout the perioperative period and has important clinical consequences. Preoperative anemia is usually regarded as no more than a surrogate marker of a patient's physical status, and it is not always adequately addressed before surgery. Postoperative anemia is a common event and occurs in 80–90% of patients who have undergone major surgery. This manuscript discusses the detection and management of preoperative anemia, the three pillars of patient blood management, perioperative anemia management, and risk stratification for anemia in the surgical setting.